THE EFFECT OF CARDIORESPIRATORY FITNESS AND FATIGUE LEVEL ON LEARNING ABILITY OF MOVEMENT COORDINATION - Erwin Setyo Kriswanto; Hari Setijono; Edy Mintarto (Jurnal Cakrawala Pendidikan, 2019)
This research aims to prove: 1) relationship between cardiorespiratory fitness with movement coordination learning ability, 2) relationship between cardiorespiratory fitness with fatigue level, and 3) relationship between cardiorespiratory fitness and fatigue level on learning ability of movement coordination. Samples were 30students of Department of Sport Education determined by purposive sampling technique.To conduct the correlational research, the instruments includeda Cardiorespiratory fitness measured by using Fitmate version 2.2, Wellness Technology a Division of Cosmed, also equipped with other supporting devices such as treadmills. Level of fatigue was measured by using the heart rate monitor of Polar brand and Stopwatch (BT Butterfly 60 Japan) while movement coordination learning ability measured by using Drawing Mirror Tracer Test. Using multiple regression analysis, it is concluded that: firstly, there is significant relationship between cardiorespiratory fitness and learning ability of movement coordination. Secondly, there is significant relationship between the level of fatigue and the learning ability of movement coordination. Thirdly, there is significant relationship between cardio respiratory fitness and level of fatigue in the learning ability of movement coordination.